If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(X + -3) + 2x = 0 Reorder the terms: 6(-3 + X) + 2x = 0 (-3 * 6 + X * 6) + 2x = 0 (-18 + 6X) + 2x = 0 Solving -18 + 6X + 2x = 0 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '18' to each side of the equation. -18 + 6X + 18 + 2x = 0 + 18 Reorder the terms: -18 + 18 + 6X + 2x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + 6X + 2x = 0 + 18 6X + 2x = 0 + 18 Combine like terms: 0 + 18 = 18 6X + 2x = 18 Add '-2x' to each side of the equation. 6X + 2x + -2x = 18 + -2x Combine like terms: 2x + -2x = 0 6X + 0 = 18 + -2x 6X = 18 + -2x Divide each side by '6'. X = 3 + -0.3333333333x Simplifying X = 3 + -0.3333333333x
| 3/x+1=5/6+x/2 | | (5/7x)-(5/6)=(1/6x) | | -x/g=18 | | 1000+250x=1500+200x | | 7y-2x=5 | | 1000+250x=1500+200 | | r+7=35 | | 9r-3=-7r-9 | | 18=2x+7 | | -0.4x=-0.8x+2 | | 5x+165=135+10x | | (8+3x)+(-5-x)= | | 8x-(2-3)=18 | | (-6x+7)-(x+2)= | | 12=2x+7 | | 24mn-16n=0 | | 100+7=15 | | 8+6y=32 | | 4x+8=72+5x | | 8(2x+3)=16x+4 | | (4x-4)(4x+6)= | | 5x+3y=13.00 | | 14x+7=28(2+x) | | a+2b=432 | | a=36-(49-3*5) | | 10x^2-15x+10=0 | | 14x+7=28(10+5x) | | v-16=-36 | | 14x+7=9(10+5x) | | a=25*2-(-16)*(-27) | | 14x+7=9(12+5x) | | -3=7y+64 |